Pyomelanin from Pseudoalteromonas lipolytica reduces biofouling - Zhenshun Zeng (Microbial Biotechnology, 2017)
Summary Members of the marine bacterial genus Pseudoalteromonas are efficient producers of antifouling agents that exert inhibitory effects on the settlement of invertebrate larvae. The production of pigmented secondary metabolites by Pseudoalteromonas has been suggested to play a role in surface colonization. However, the physiological characteristics of the pigments produced by Pseudoalteromonas remain largely unknown. In this study, we identified and characterized a genetic variant that hyperproduces a dark‐brown pigment and was generated during Pseudoalteromonas lipolytica biofilm formation. Through whole‐genome resequencing combined with targeted gene deletion and complementation, we found that a point mutation within the hmgA gene, which encodes homogentisate 1,2‐dioxygenase, is solely responsible for the overproduction of the dark‐brown pigment pyomelanin. In P. lipolytica, inactivation of the hmgA gene led to the formation of extracellular pyomelanin and greatly reduced larval settlement and metamorphosis of the mussel Mytilus coruscus. Additionally, the extracted pyomelanin from the hmgA deletion mutant and the in vitro‐synthesized pyomelanin also reduced larval settlement and metamorphosis of M. coruscus, suggesting that extracellular pyomelanin released from marine Pseudoalteromonas biofilm can inhibit the settlement of fouling organisms.